Assessment of the Psychometric Properties of the Holland Sleep Disorders Questionnaire in the Iranian Population. (14th March 2022) - Khazaie, Habibolah; Jalali, Amir; Mohammadi, Reza; Chehri, Azita; Khazaie, Amirhossein
Abstract : Background . Assessing sleep disorders and understanding their causes are essential for the proper treatment and management of the disorders. The Holland Sleep Disorders Questionnaire (HSDQ) is a self-assessment questionnaire that measures sleep problems and symptoms based on the six categories of sleep disorders described in the International Classification of Sleep Disorders-2 (ICSD-2). The aim of this study was at validating and assessing the psychometric properties of the HSDQ in Iranian adults. Method . The study was carried out as a methodological and validation work. The guidelines for translation and cultural adaptation of patient-reported outcome measures were followed for the translation and the cultural validation of the tool. To examine construct validity, exploratory factor analysis (EFA) with 216 participants and confirmatory factor analysis (CFA) with 355 participants were used. As to the reliability, the test-retest method and, as to internal consistency, Cronbach's alpha were employed. Data analyses were done in SPSS-25 and LISREL-8. Results . The CFA and EFA results confirmed the tool with six factors and 31 items. The R 2 index of the model was 0.99, which indicated that 99% of changes in the dependent variable (adults' sleep problem) were attributed to the independent variable (the 31 items). In other words, 0.99 of the changes in the dependent variable were due to the independent variables. The main indices of CFA (χ 2 / DF = 2.65, CFI = 0.91 NNFI / TLI = 0.92 GFI = 0.81, REMSEA = 0.043, R 2 = 0.99 ) were acceptable. In addition, a correlation coefficient below 0.05 was considered as significant. Reliability of the tool based on internal correlation (Cronbach's alpha) was in the 0.701–0.924 range for the subscales and equal to 0.789 for the whole tool. Conclusion . In general, the results showed that the Farsi version of HSDQ (six factors and 31 items) had acceptable and applicable indices and it can be used as a valid tool in the Iranian society. The tool can be used as a reliable tool in different fields of medical sciences.